50-Year history of congenital hemoptysis: A case of gastro-duodenal oral choristoma. Issue 2 (March 2016) - Aluko-Olokun, Bayo; Olaitan, Ademola A.; Aluko-Olokun, Oluseun A.
Abstract: A case of life-long hemoptysis in a 50-year-old woman found to be caused by a bleeding gastro-duodenal oral choristoma is presented. The rare nature of the condition could have led to it being misdiagnosed. She had been managed as a case with more common causes of hemoptysis. The clinical value of lessons learned from this case lies in the infinite nature of possible causes of symptoms and signs observed in patients; every case should be treated as unique, or potentially so. The step-by-step scientific method without undue bias in favor of the use of inexhaustive checklists, of causes of symptoms and signs, works best for management of every patient, as all cases are unique. Causes of hemorrhage can hardly be exhaustively listed.